2007
DOI: 10.1183/09031936.00140506
|View full text |Cite
|
Sign up to set email alerts
|

Early discharge of patients with pulmonary embolism: a two-phase observational study

Abstract: The aim of the present study was to assess whether patients with pulmonary embolism (PE) could be managed as outpatients after early discharge from hospital using low molecular weight heparin instead of remaining as in-patients until effective oral anticoagulation was achieved.Phase 1 of the study identified criteria for the safe discharge of selected patients; phase 2 treated a cohort of low-risk patients with PE as outpatients with tinzaparin using existing deep venous thrombosis services.In phase 1, 127 (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 33 publications
4
76
0
2
Order By: Relevance
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 11 studies were included in our systematic review. Eight were prospective cohort studies [8,[11][12][13][31][32][33][34]] and 3 were randomized controlled trials (RCT's) [16,17,35]. Furthermore, 2 studies did not report outcomes at 3 months and could not be used in our pooled meta-analysis [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the studies exclusively included patients that were treated entirely as outpatients. Two studies included patients that were discharged early [16,32] and 1 study reported early discharge and outpatient groups separately [34]. Early discharge was generally defined as inpatient stay of 1-3 days [16,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term outcomes were available for only six studies: no patient died in the first 7-10 days, seven patients had recurrent VTE and two experienced major bleeding [20,22,[29][30][31][32]. Data on the long-term outcome were available for nine out of the 11 studies [9,19,22,27,29,31,32,35,37].…”
Section: Resultsmentioning
confidence: 99%
“…No RCTs were identified. Seven observational studies had a prospective cohort design [19,20,22,27,31,35,37]. No study fulfilled the criteria required for high quality (table 1).…”
Section: Resultsmentioning
confidence: 99%